Pengawasan Kedisiplinan Peserta Didik di SMP IT Fathona Pakjo Palembang (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to understand the Discipline Supervision of Students at SMP IT Fathona Pakjo Palembang. The type of research uses a qualitative research approach. The key informant in the Discipline Supervision of Students at SMP IT Fathona Pakjo Palembang is the school principal. Supporting informants in this research include the Vice Principal for Student Affairs and teachers at SMP IT Fathona Pakjo Palembang. Data collection techniques in qualitative research involve interviews, observations, and documentation. After collecting the data, the author analyzes and explains the data. The data analysis model used in this research consists of steps for data collection, data presentation, verification, and conclusion drawing. The results indicate that the supervision of student discipline at SMP IT Fathona Pakjo Palembang is carried out effectively, through several stages namely monitoring student discipline, checking student discipline, guidance and direction on student discipline, disciplinary actions for students, and corrective actions for student discipline.